Uwarunkowania zarządzania własnym zdrowiem - Mruk, Henryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The state will not be able to finance the growing needs of patients in the field of health protection. Patients will increasingly finance the use of medical services from their own income. In this situation, more than ever they will also be interested in care for their own health. Conclusions resulting from the development of behavioral economics can be helpful for patients in managing their own health. The introduction of pharmaceutical care to pharmacies in Poland can effectively help patients maintain their health and quality of life
Keywords: zdrowie osobiste; zarządzanie zdrowiem osobistym; ekonomia behawioralna; zdrowie; awans